2018
DOI: 10.1002/mabi.201800016
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polymer Design that Inhibits Aggregation and Facilitates Insulin Refolding: Mechanistic Insights and Importance of Hydrophobicity

Abstract: The synthesis of a zwitterionic polymer, poly-sulfobetaine (poly-SPB), which shows remarkable efficiency in the suppression of insulin aggregation is described. Hydrophobic modification of the polymer results in almost complete inhibition at very low polymer concentrations. Further studies reveal that these polymers facilitate the complete retention of insulin's secondary structure, which is otherwise lost after incubation. Refolding studies show that addition of polymers to preaggregated insulin sample leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…11c). 322 The aggregation of insulin was suppressed by the addition of the copolymers, and no turbidity could be seen even after prolonged incubation at 37 1C for 24 h, which would otherwise aggregate within 7 hours of incubation. The addition of small doses of hydrophobic monomers to the homopolymer of poly-SPB increased the protection efficiency significantly.…”
Section: Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…11c). 322 The aggregation of insulin was suppressed by the addition of the copolymers, and no turbidity could be seen even after prolonged incubation at 37 1C for 24 h, which would otherwise aggregate within 7 hours of incubation. The addition of small doses of hydrophobic monomers to the homopolymer of poly-SPB increased the protection efficiency significantly.…”
Section: Reviewmentioning
confidence: 88%
“…321 NMR can be used to examine the interaction of any excipient with the protein by observing the individual amino acid residues to reveal the mode of aggregation, or the protection from aggregation. 322 In a recent study by Taraban et al, water NMR was compared with other characterization techniques such as SEC, DLS, and others, and NMR outperformed them, proving to be more effective and sensitive for detecting changes in soluble and insoluble protein aggregates. 221 Time-consuming investigation of the relaxation analysis, peak assignments, and the inability to characterize larger aggregates are some of the limitations of solution NMR.…”
Section: Circular Dichroism (Cd) Spectroscopy CD Is a Powerful Technique Used In The Investigation Of Different Orders Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its unique chain structures and high biocompatibility, PSPB has been associated with unique properties such as cryopreservation and has been used for anti-bio adherent coatings . Moreover, in a previous work, we found that this polyampholyte exhibits a protein aggregation inhibition property, owing to its weak and reversible interaction with protein molecules, thereby acting as a molecular shield. This phenomenon enables PSPB to assist proteins in the retention of their secondary structures and suppresses fibrillation of the protein, even under severe stress. To utilize this kind of dual thermo-responsive polymer for biomedical applications such as protein delivery, PSPB was chosen along with COOH-PLL in this study for the graft polymer system.…”
Section: Introductionmentioning
confidence: 90%
“…The nanogels showed better efficacy than that of linear polymers as the nanogels are considered to behave as artificial molecular chaperones, which protect the proteins against thermal aggregation. Furthermore, the potential of poly-SPB in suppressing insulin aggregation process has been demonstrated . They have synthesized a series of copolymers of sulfobetaine (SPB) with a hydrophobic monomer butyl methacrylate (BuMA) by changing the feed ratio.…”
Section: Effects Of Polymers On Amyloid Protein Aggregationmentioning
confidence: 99%